TRANSFORMATIONAL LEADERSHIP: MILLENNIAL LEADERSHIP STYLE IN INDUSTRY 4.0 - Suyanto, Umar Yeni; Mu?ah, Mu?ah; Purwanti, Ika; Sayyid, Mokhtar (Department of Management, 2019)
This article analyzes how transformational leadership roles reflect the character of the millennial generation in the fourth industrial revolution. As the development of technology advances rapidly, people take advantages of it not only for education and research development but also for need fulfillment. In industry 4.0, technological competition seems to have great impact on company performance. The data obtained from the Ministry of Communication and Information show that the growth of online retail business in Indonesia was relatively high (36%) from year 2010 to 2013. The rate was twice higher than that of The Phillipine?s and Malaysia?s, even 3.5 times higher than Singapore?s. The number of Internet users in 2014 was 83.6 millions, which showed approximately 33% growth rate in Internet penetration. The Central Statistics Agency (BPS) reports that 50% of workers in Indonesia are less than 30 years old. In other words, the millennials are mostly active workers who have constant access to information and technology. This is a library research gathering and analyzing information from related references and theories, which have become the basic foundation and sources in analyzing problems in this research. The results revealed that transformational leadership can be improved and optimized by implementing the four primary factors, namely idealized influence, intellectual stimulation, inspirational stimulation, and individualized consideration.